Wage polarization in a high-inequality emerging economy: The case of South Africa - Haroon Bhorat; Kezia Lilenstein; Morné Oosthuizen; Amy Thornton (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Earnings growth in South Africa displayed a U-shaped pattern across the earnings percentiles between 2000 and 2015, resembling wage polarization in the industrialized world. We investigate whether the drivers of this example of wage polarization in an emerging economy resemble those explored for industrialized ones. These are: skills-biased technical change; changing sectoral composition; the role of labour market institutions; and how occupational task content interacts with technology. A recentred influence function regression is run on a series of South African labour force datasets merged with the Occupational Information Network to explore the relevance of these four frameworks for explaining earnings inequality between 2000 and 2015. Labour market institutions are crucial to the U-shape. Wage growth at the bottom end has mainly been shored up by minimum wages, without which we expect wage growth there would have resembled the weaker growth of the middle of the distribution.
Keywords: J31; J24; C21; 330; inequality; minimum wages; recentred influence function; South Africa; tasks; wagepolarization